Integration of Green Infrastructure Planning Principles into Spatial Planning - Monteiro, Renato Miguel Carromeu (2022)
Green infrastructure is a strategically planned network of natural and semi-natural areas that are designed and managed to deliver a wide range of ecosystem services. It incorporates green and blue spaces and other physical features in terrestrial and marine areas. In addition to its ecological benefits, green infrastructure serves as a planning tool that promotes social and economic benefits, resulting in competitive, resilient, sustainable, and inclusive metropolitan communities. Since its initial appearance in the literature in the 1990s, the concept of "green infrastructure" has become widely used the academia, political actors, and policymakers. However, despite the extensive literature on the subject, there is still a level of complexity associated with the concept of "green infrastructure" that makes its implementation at the local level more difficult. Because of that, this research aims to investigate which green infrastructure planning principles should be considered in spatial planning and how practitioners and policy makers can integrate them into policies and environmental planning. To accomplish that, three re-search questions were answered: (1) What green infrastructure planning principles should be considered in spatial planning? (2) What are the views and priorities of practitioners and urban planners on green infrastructure planning principles? (3) How are these principles being integrated into spatial planning? To answer these questions, this research follows a transdiscipli-nary approach and participatory methods applied to a case study - Lisbon Metropolitan Area -, such as an integrative literature review, an analytic hierarchy process, desk research, and spatial plan document analyses. Findings show that the green infrastructure planning principles that must be incorporated into spatial planning are connectivity, multifunctionality, applicability, integration, diversity, multiscale, governance, and continuity, with the principles of connec-tivity, multifunctionality, governance and multiscale being the most cited in the literature, and applicability the least considered. Furthermore, the green infrastructure planning principles considered most important for professionals in the Lisbon Metropolitan Area, resulting from the exercise of analytic hierarchy process, were connectivity, followed by multifunctionality and applicability. As a result of the last exercise, although the principles of connectivity, diversity and applicability stood out, the results showed that, moving into practice, all municipalities analysed in this study present significant challenges regarding the integration of green infra-structure planning principles into their planning plans and territorial planning strategies. Be-cause of that, this work encourages further research on this topic in general and especially recommends investigating cases in other countries, at different scales. This research is recommended for practitioners to help them find opportunities and define priorities for planning, implementing, and monitoring green infrastructure in their organizations.